Flexible Working Arrangement dan Kinerja Karyawan: Systematic Literature Review: Flexible Working Arrangements and Employee Performance: A Systematic Literature Review - Almas Nur Falah; Fahmi Aqil Saputra; Eriko Dwi Handoko; Dani Rizana (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to systematically review the influence of FWA on employee performance by considering various mediating and moderating factors that influence the relationship. Using a Systematic Literature Review (SLR) approach referring to the Kitchenham & Charters (2007) guidelines, the research process includes three main stages: planning, conducting, and reporting. Of the 450 articles identified through the Scopus, Google Scholar, Emerald Insight, and Garuda Dikti databases, 10 articles that met the inclusion criteria were analyzed in depth using the PRISMA method. The synthesis results indicate that FWA has a positive effect on employee performance, especially when supported by work-life balance and work engagement as mediating variables. Several studies confirm that flexible work schedules and locations can improve employee well-being and work engagement, ultimately impacting productivity. However, the positive effects of FWA are not universal; organizational context, supervisor support, and technological readiness have been shown to be important factors determining its effectiveness. Studies also found that without adequate organizational support, FWA can lead to negative impacts such as social isolation, stress, and decreased job satisfaction. Overall, the results of this study confirm that FWA is a relevant human resource management strategy in the modern work era. Effective FWA implementation requires a balance between flexibility policies and strengthening organizational support systems, technology, and a collaborative work culture. These findings provide theoretical contributions by strengthening understanding of the relationship between FWA and performance, while also providing practical implications for organizations in designing adaptive, productive, and sustainable flexible work policies.